1991
DOI: 10.1128/jvi.65.5.2340-2350.1991
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and genetic variation in influenza A (H1N1) virus isolates recovered from a persistently infected immunodeficient child

Abstract: Antigenic and genetic variations have been analyzed in eight consecutive isolates recovered from a child with severe combined immunodeficiency syndrome persistently infected with naturally acquired type A (HlNl) influenza virus over a 10-month period. Hemagglutination inhibition reactions and T1 oligonucleotide fingerprinting demonstrated that these viruses were related to strains causing outbreaks in the United States at that time (1983 to 1984) but that antigenic and genetic differences between consecutive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(23 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…These changes in tissue tropism could be a consequence of escaping mechanisms of the virus associated with the immune pressures driven by vaccination protocols for IBV [39,40]. Furthermore, it has been demonstrated that immunity is not the only selective pressure on IBV [41] and the genetic diversity in viral isolates is attributed to shifts in population equilibrium of the replicating viral genomes even in the absence of immune selection pressure [42]. Such divergence between genotype and predominant pathotype or tissue tropism has also been reported in an IBV isolate from Egypt (Egypt/F/ 03), which, despite being classified as Massachusetts, showed a marked nephropathogenicity in experimentally infected SPF chickens [43].…”
Section: Discussionmentioning
confidence: 99%
“…These changes in tissue tropism could be a consequence of escaping mechanisms of the virus associated with the immune pressures driven by vaccination protocols for IBV [39,40]. Furthermore, it has been demonstrated that immunity is not the only selective pressure on IBV [41] and the genetic diversity in viral isolates is attributed to shifts in population equilibrium of the replicating viral genomes even in the absence of immune selection pressure [42]. Such divergence between genotype and predominant pathotype or tissue tropism has also been reported in an IBV isolate from Egypt (Egypt/F/ 03), which, despite being classified as Massachusetts, showed a marked nephropathogenicity in experimentally infected SPF chickens [43].…”
Section: Discussionmentioning
confidence: 99%
“…When a mutant spectrum harbors an ample repository of variants, selection of genome subsets in a new environment can be very rapid. Astonishing rates of evolution of consensus sequences in vivo, of 10 Ϫ2 substitution per site per year or even higher, can be attained (87,136,311,341,473,698,753). It should be appreciated that such rates of evolution are 10 6 -to 10 7 -fold higher than the average rates estimated for cellular genes during long-term evolution (the values and implications are reviewed in references 189 and 376).…”
Section: Population Equilibrium Apparent Stasis and Rapid Evolutionmentioning
confidence: 99%
“…The number of infectious particles shed by an infected host determines the probability of transmission to susceptible hosts (Section 7.2), and of producing an emergence in a new host species. Viral population numbers and the number of transmissible particles can be largely amplified in immunocompromised individuals, and have been termed super-spreaders; they can contribute large amounts of variant viruses to the transmission lottery (Rocha et al, 1991;Paunio et al, 1998;Gavrilin et al, 2000;Khetsuriani et al, 2003;Small et al, 2006;Odoom et al, 2008;Woolhouse, 2017). Concerning the recipient hosts, the higher the number of potentially susceptible hosts that come into contact with an infected donor, the higher the probability of establishment of an emergent infection.…”
Section: Factors In Viral Emergencementioning
confidence: 99%